Propagule supply limits grazer richness equally across a resource gradient. Issue 1 (24th January 2014) - Lee, Sarah C.; Bruno, John F.
Abstract : Although the independent effects of propagule supply and resource availability on species diversity are widely recognized, there are conflicting predictions of how resource availability affects the strength of propagule supply. To determine how propagule supply and resource availability interact to control species richness, we compared the effects of grazer propagule additions on grazer and algal assemblages across an experimental gradient of algal productivity. Different levels of algal productivity (i.e., replacement rate of grazers' food resource) were maintained by manipulating light. Despite light‐driven changes in algal standing biomass and diversity, algal resource availability had no effect on propagule limitation of grazer species richness, nor on grazer community composition. Instead, augmenting grazer propagule supply had equally strong, positive effects on grazer richness at all levels of algal resource availability. Although there was evidence for competition and resource limitation in the high propagule supply/low resource treatment, competition was evidently too weak or the experimental duration was too short to lead to competitive exclusion and changes in species richness, evenness, and composition. Our results highlight potential differences in resource use between sessile producers and mobile grazers. Unlike plants that consume inorganic nutrients and light whose renewal is positive, donor‐controlled, and identity‐fixed, animals consume dynamic resources that can respond to consumption by increasing growth rates, or going extinct and being replaced by other species, as we observed in the replacement of easily ingested green algae by less preferred red algae. The dual nature of these dynamic resources may consequently weaken the link between resource renewal rates and propagule limitation in animal communities.